University-Industry Collaboration For Manpower Planning And The Challenges Of Economic Development - Obasi, Obasi; Kelechi, Kenneth (Publikasi Indonesia, 2023)
The development of manpower aimed at addressing the prevailing and future needs of a given society is a good reason for designing and structuring collaboration between universities and industries. Using a qualitative research design, this article explored the university-industry collaboration for manpower planning and the challenges of economic development in Nigeria. It looked at the concept of university education as a private and social investment that has a limitless rate of returns to both the individual recipient and the society. It also discussed the relationship between economic development and manpower development planning and highlighted that economic development which is a deliberate process of sustained quality improvement of the people requires proper planning, at the center of which is manpower development planning. Furthermore, the critical roles universities and industries in Nigeria have to play in producing the skills needed for industries and national development were also examined. These roles include producing high-level and middle level manpower in order to address socio-economic challenges, boosting the acquisition of skills to tackle the mismatch between skills of the available workforce and job vacancies, and championing ideas and innovations to facilitate access to new markets. The article suggested a number of strategic approaches to foster a stronger collaboration of universities with industry. These strategies include among others an establishment of a consultative process where the voice of relevant business managers is given adequate consideration in curriculum development in order to ensure that the academic programs of universities are tailored to the needs of the industries.